Reflections on the society’s reaction towards rape victims in Delhi City - Hetu Vibha (Temida)
In general, most people display stronger beliefs in ‘aggravated rape‘ or ‘real rape‘; including victims of such rape cases who often identify themselves as ‘rape victims’ than the victims of ‘simple rape’, where none of the aggravating circumstances are present. Despite myths to the contrary these ‘simple rape’ cases in fact make up the majority of cases. This article considers the implications of ‘real rape‘ and demonstrates how notions about what a ‘typical rape‘ should be, in the form of rape myths, directly impact on societal attitudes towards rape victims and how the media continue to reinforce and perpetuate the notion of real rape through their selective reporting of ‘serial rape’, ‘stranger rape’ or especially ‘violent rapes’.